(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the issues of the importance of spirituality and education in reducing poverty. The paths leading to future economic development, social stability and spiritual growth are indicated. The issues of increasing the effectiveness of education and the formation of spirituality are touched upon. Also, existing problems and their solutions are proposed.